The effect of market-to-book ratio, asset structure, and earning after tax on the level of leverage in non-financial companies listed in Indonesia Stock Exchange 2007-2012 - Rezza Arlinda Sarwendhi; Agus Samekto (Universitas Hayam Wuruk Perbanas, 2014)
The theory of capital structure has experienced remarkable development. This development enables companies to have many options to consider the external factors in determining various compositions of the companies’ debts and equities. In this study, the researcher uses theoretical basis of Market Timing Theory (MTT) introduced by Baker and Wurgler (2002). The result of this study indicates that marketto-book ratio has a negative effect on the level of company leverage. This is also proven on the factors of earning after tax and asset structure of the company. The implication of this study is that when the company obtains lower level of leverage, there will be overvalue on the stock price, and it would be the right time for the company to release the shares.